2014
DOI: 10.1093/nar/gku612
|View full text |Cite
|
Sign up to set email alerts
|

Protein Hit1, a novel box C/D snoRNP assembly factor, controls cellular concentration of the scaffolding protein Rsa1 by direct interaction

Abstract: Biogenesis of eukaryotic box C/D small nucleolar ribonucleoprotein particles (C/D snoRNPs) involves conserved trans-acting factors, which are proposed to facilitate the assembly of the core proteins Snu13p/15.5K, Nop58p/NOP58, Nop56p/NOP56 and Nop1p/Fibrillarin on box C/D small nucleolar RNAs (C/D snoRNAs). In yeast, protein Rsa1 acts as a platform, interacting with both the RNA-binding core protein Snu13 and protein Pih1 of the Hsp82–R2TP chaperone complex. In this work, a proteomic approach coupled with func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(96 citation statements)
references
References 64 publications
(110 reference statements)
5
91
0
Order By: Relevance
“…As mentioned previously, ZNHIT6 and ZNHIT3 are snoRNP biogenesis factors that interact with NUFIP1 and the AAA+ ATPases91415. ZNHIT1 and INO80B/ZNHIT4 are components of chromatin remodelling complexes SRCAP and INO80, respectively, both of which also harbour a RUVBL1 and RUVBL2 module7.…”
Section: Resultsmentioning
confidence: 87%
“…As mentioned previously, ZNHIT6 and ZNHIT3 are snoRNP biogenesis factors that interact with NUFIP1 and the AAA+ ATPases91415. ZNHIT1 and INO80B/ZNHIT4 are components of chromatin remodelling complexes SRCAP and INO80, respectively, both of which also harbour a RUVBL1 and RUVBL2 module7.…”
Section: Resultsmentioning
confidence: 87%
“…Regions 223-260 in NUFIP1 and 233-266 in Rsa1p are highly homologous and correspond to the conserved PEP motif, which directly contacts the helix a3 of the core protein SNU13/Snu13p (Rothe et al, 2014b). Point mutations of conserved residues in the PEP motif produced similar yeast two-hybrid (Y2H) effects in yeast and human.…”
Section: Introductionmentioning
confidence: 99%
“…This result demonstrated that association of Rsa1p, which occurs early on the nascent transcript (54), persists at least until the +12/+18 cleavage steps. Of note, both in the input and IP fractions no long PCR products corresponding to unspliced forms were detected, confirming the rapid elimination of the intron prior to 3΄-end processing.…”
Section: Resultsmentioning
confidence: 78%